Submandibular gland is a suitable site for alpha synuclein pathology in Parkinson disease. (January 2019) - Shin, Junghwan; Park, Sung-Hye; Shin, Chaewon; Kim, Ji-hoon; Yun, Tae Jin; Kim, Han-Joon; Jeon, Beomseok
Abstract: Objective: To validate the role of α-synuclein (AS) pathology in submandibular gland (SMG) as a biomarker for Parkinson disease (PD). Methods: We performed ultrasonography (USG) guided core needle biopsy of SMG in PD patients and procured SMG biopsy tissues or surgical excision specimens from non-PD patients as controls. Then, we compared AS deposition in the SMG tissues between the PD patients and the controls. We recruited 16 PD patients in this study. In each individual, two core needle biopsy tissues were obtained from the left submandibular gland under USG guidance. Fourteen sex and age-matched controls who did not have PD and dementia but received a core needle biopsy or surgical resection of the SMG due to SMG diseases were procured from the pathology archive. Biopsy tissues and surgical specimens were immuno-stained with serine 129 phosphorylated AS (pAS) antibody for microscopic examination. pAS deposition in neural structures such as ganglion cells and neurites was considered as positive. Results: No serious complication occurred during and after the SMG biopsy. We found glandular parenchyma and neural structures in all biopsied SMG tissues from the patients and the controls. Nine out of 16 PD patients (56.2%) were positive for pAS staining, while none of the controls were positive (0%). Conclusions: SMG core needle biopsy can reliably and safely obtain sufficient glandular parenchyma and neural structures to evaluate the α-synuclein pathology. AS pathology in SMG has high specificity and good sensitivity as a biomarker for PD. Highlights: SMG core needle biopsy is safe and technically feasible to reliably obtain neural structures in living PD patients. pAS staining in SMG is highly specific in PD patients (100%). Submandibular gland is a suitable tissue for studying AS pathology in PD.